Avaliação da genotoxicidade de extratos de boldo (Plectranthus ornatus) e graviola (Annona muricata) através do ensaio cometa e do teste de micronúcleo em linfócitos humanos - Rocha, Rodrigo dos Santos (2016)
The use of vegetables with medicinal purposes contributes significantly to the care of the primary needs of assistance to health due to difficult access of the population to medical and pharmaceutical assistance, the high cost of manufactured medications and a tendency for people to use natural origin products. However, technical and scientific information about most of them, particularly with respect to the genotoxic potential, are still insufficient so that the use can be considered safe. In this context, the aim of this study was to evaluate the genotoxic effects of boldo extracts (Plectranthus ornatus) and soursop (Annona muricata), through the comet assay and micronucleus test in human lymphocytes with cytokinesis blocking (MNCtB). The tests were performed on human lymphocyte cultures exposed to the extracts in three concentrations: 1.000μg/ml, 500μg/ml and 250μg/ml. Hydrogen peroxide (1mM) was used as a positive control in the comet assay and vincristine sulfate (1mM) in MNCtB. As a negative control, 40% ethanol was used in both tests. The processing of the material for the comet assay and MNCtB was done according respectively to the protocols Tice et al. (2000) and Fenech (1993). The comet assay was performed in five repetitions being computed, in each of them, 100 comets in a total of two blades. For MNCtB three repetitions were performed and 1.000 binucleate lymphocytes were computed per slide. The occurrence of DNA damage (comet assay) did not differ between the cell of the cultures exposed to different concentrations of boldo extracts from each other nor compared to the negative control. Higher occurrence of micronuclei (MNCtB) was observed in the cell of the cultures treated with the extract at concentrations of 1.000μg/ml and 500μg/ml when compared to the negative control (p<0.05) and cultures treated with the extract concentration of 250μg/ml. The soursop extracts at concentrations of 1.000μg/ml to 500μg/ml induced damage occurrence to the DNA significantly higher than that observed in the negative control and cultures treated with extract at a concentration of 250μg/ml (p<0.001). The conditions in which this study was performed, the obtained results allow concluding that: 1) boldo extracts are not effective in inducing DNA damage, but depending on the concentration, they present clastogenic and/or aneugenic effects; 2) soursop extracts induce DNA damage under certain concentrations. The results of this study strongly raise the achievement of other addressing the issue, so that the actual genotoxic potential of vegetables analyzed here can be established.